2021
DOI: 10.1111/irv.12867
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of influenza‐associated infections among hospitalized patients with acute respiratory infections, Egypt national surveillance system, 2016‐2019

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…Despite the significantly lower fatality rate from influenza than SARS-CoV-2 found in this study, it is still higher than the rate reported during the inter-pandemic period [ 26 ]. Furthermore, high rates of ICU admissions and mechanical ventilation due to influenza were reported in this study.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Despite the significantly lower fatality rate from influenza than SARS-CoV-2 found in this study, it is still higher than the rate reported during the inter-pandemic period [ 26 ]. Furthermore, high rates of ICU admissions and mechanical ventilation due to influenza were reported in this study.…”
Section: Discussioncontrasting
confidence: 68%
“…This pattern is different to that reported by Fahim et al in Egypt during the pre-pandemic phase, with higher fatality rates and severe outcomes among older people and a predominance of A/H1 26 . Some studies suggest that the A/H3 virus has declined in its ability to efficiently infect susceptible hosts but, according to this and other studies, influenza-associated hospitalisations and deaths are highest during seasons where A/H3 dominates [ 26 , 27 ]. Due to reduced influenza viruses circulating in 2020, the severity of the A/H3 subtype could have changed due to a prolonged absence of natural exposure to influenza viruses.…”
Section: Discussionmentioning
confidence: 94%
“…[ 1 ] In Egypt, 17.3% of hospitalized patients with acute respiratory infections included one or more types of influenza viruses. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that the largest proportion of patients with SARS-CoV-2/Flu co-infection occurs in the middle age group; in addition, most of the patients had experienced mild symptoms and were treated at home. This could reflect characteristics of influenza viral infection that affects mainly young ages and does not usually require hospitalization [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in different countries reported an increase or decrease in fatality rates compared to SARS-CoV-2 infection [ 2 , 21 23 ]. This study reported higher rates of fatality among hospitalized patients with coinfection compared to rates of fatality from SARS-CoV-2 and influenza infections in Egypt [ 17 ]. The severity of the disease course and high fatality rates reported in this study could be related to the small number of hospitalized patients with coinfection, the high prevalence of comorbidities among them, or delay in influenza testing which could lead to delay in the effective case management.…”
Section: Discussionmentioning
confidence: 99%